ANALISIS LAPORAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (LAKIP) BERBASIS VALUE FOR MONEY PADA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BUTON SELATAN - Mahmuda, Dewi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study aims to determine the value for money-based government agency performance accountability report (LAKIP). The method is descriptive qualitative approach. The results is economic ratio in 2021 and 2022 all programs were declared economical. The 2021 and 2022 efficiency ratios show that the performance indicators of the percentage of job seekers placed and the percentage of labor productivity levels are declared inefficient and the performance indicators of the average percentage of the results of the achievement of the implementation of OPD support programs are declared efficient. The effectiveness ratio of 2021 and 2022 shows that the performance indicator of the percentage of job seekers placed is declared ineffective, the percentage of labor productivity level is declared effective and the average percentage of the results is achievement of the implementation of OPD supporting programs is declared balanced effective, 2022 performance percentage job seekers placed and of labor productivity level is declared effective and the performance indicator of the average percentage of the results of the achievement of the implementation of OPD supporting programs is declared balanced effective.